Effect of the university on the social entrepreneurial intention of students - Carlos Bazan; Hannah Gaultois; Arifusalam Shaikh; Katie Gillespie; Sean Frederick; Ali Amjad; Simon Yap; Chantel Finn; James Rayner; Nafisa Belal (New England Journal of Entrepreneurship (NEJE), 2020)
Purpose The study aims to test the applicability of a variant of the model proposed by Hockerts (2017) for assessing the social entrepreneurial intention (SEI) of male and female students. It extends the model by incorporating the university's environment and support system (ESS) as an additional more distal construct. The university's ESS, coupled with the experience with social, cultural and environmental issues can affect SEI by influencing the more proximal precursors of empathy towards others, perceived self-efficacy, perceived community support and social, cultural and environmental responsibility. Design/methodology/approach A structured non-disguised questionnaire was administered to students at a Canadian university. A sample of 485 usable responses was analysed by means of second-order structural equation modelling. Findings The results provide confirmation that the proposed model is a multi-group invariant and appropriate for analysing the SEI of male and female students. They also show that the university's ESS helps predict SEI indirectly through the complete mediation of the more proximal antecedents. Research limitations/implications The questionnaire is limited to universities with social innovation and entrepreneurship initiatives. Practical implications Outcomes of the study can help universities assess the efficacy of their social innovation and entrepreneurship initiatives for instilling a social entrepreneurial mind-set in students. Consequently, universities will be better equipped to raise the perceptions of venture feasibility and desirability, thus increasing students' perceptions of opportunity. Originality/value The study advances the social entrepreneurial knowledge of the university's effect on the precursors of SEI.
Keywords: 650; Social enterprise; Social entrepreneurial intention; Theory of planned behaviour; University environment and support system